OBJECTIVES AND GOALS POLICY OF GURU GARIS DEPAN PROGRAM TO IMPROVE THE BASIC EDUCATION QUALITY - Fitriyani Fitriyani; Bedjo Sudjanto; Suryadi Suryadi; Matin Matin (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this study was to obtain the results of the evaluation of the input for the GGD program related to the participants, the committee, and the GGD technical guidance. The research method is descriptive qualitative because this research wants to get input information from the GGD program policies. Data collection techniques used open interviews, documents, and documentation studies. Data sources are the GTK Directorate, Kemdikbud, Head of the Ministry of Education and Culture's HR Bureau, the GGD committee. The data analysis technique used data triangulation. The results of the study concluded that the GGD participants had followed a series of procedures stipulated in the GGD policies, the committee had set requirements according to the needs of the GGD implementation, and technical guidance was provided so that the GGD participants were ready to work in the 3T areas. All the resources involved in the GGD program, from the central to the participating regions, did this program well. The results of the study recommended providing activities that can improve the professionalism of GGD participants